Endogamous Marriage among Immigrant Groups: The Impact of Deportations under Secure Communities - Cynthia Bansak; Sarah Pearlman (Global Labor Organization (GLO), 2021)
We investigate the impact of removals under the Secure Communities (SC) program on the marriage patterns of immigrant women living in the U.S. where endogamous marriage is the dominant form of partnership. We focus on enforcement by MSA and country of origin and find evidence that deportations increase overall marriage rates, increase the likelihood of endogamous marriage, decrease rates of exogamous marriage to immigrants from other countries and have indeterminate effects on marriage to natives. When examining channels for behavioral responses, we find evidence pointing towards the desire to mitigate the risk of deportation through the increased importance of networks.
Keywords: J13; J15; K37; 330; Immigration Enforcement; Marriage; Endogamy; Secure Communities